Three-dimensional scanner with a modified evaluation method for measuring hand edema subtitle: an idea for accurate evaluation and preliminary fundamental and clinical validation. Issue 1 (28th February 2023) - Aoki, Shimpo; Nagano, Hisato; Kiyosawa, Tomoharu; Tsuda, Yoshifumi; Izumiyama, Ko
Abstract: Acute hand edema often results in loss of fine hand motor activities, especially without appropriate care. There is still no reliable and easy to use method to measure hand edema. In this study, we tested a handheld three-dimensional (3D) scanner on plastic male and female hand models using a whole hand measuring method (WM) and a modified method (MM) which excluded fingers. We evaluated the intra-rater reliability and inter-rater reliability and compared the measured volumes to computed tomography (CT) findings. Statistical analysis showed that the 3D scan method was valid and reliable for both WM and MM methods. In WM, intra-rater and inter-rater reliability were 0.97 and 0.84, with 95% confidence interval (CI) of 0.87–1.00 and 0.61–0.94, respectively. In MM, intra-rater and inter-rater reliability were 0.96 and 0.83, with 95% CI of 0.84–1.00 and 0.61–0.94, respectively. In comparison to the CT, the differences between 3D scan and CT in the male model volumes were 30.35 ± 2.70 cm 3 (mean ± standard deviation) for WM and 11.60 ± 2.07 cm 3 for MM. In the female model, the differences were 18.92 ± 2.66 cm 3 and 11.18 ± 2.35 cm 3, respectively. In both models, MM was significantly more accurate than WM ( p < 0.001). When used in a clinical case, the scanner recorded changes in actual volume through the course of treatment. This cost-effective handheld 3D camera can be a reliable tool for evaluating hand edema even in cases of acute injury.